GAYA PENGASUHAN ORANG TUA, INTERAKSI SERTA KELEKATAN AYAH-REMAJA, DAN KEPUASAN AYAH - Krisnatuti, Diah; Putri, Husfani Adhariani (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
The aim of this research was to analyze the correlation among parenting styles, interaction and attachment of father-adolescence, and father’s satisfaction. This study involved 60 fathers, devided into 30 fathers with male children and 30 fathers with female children who aged 12-14 years. Data was analyzed by descriptive, independent sample t-test, and Pearson corellation. The result showed that mostly adolescent perceived their parents as democratic parenting style. Mostly, communication pattern between father and adolescent was conversation-orientation, while the communication type was consensual. The mean of father-adolescent interaction in a day was 0,47 hours for male and 0,64 hours for female adolescent. There was positive significant between democratic parenting style with communication pattern of conversation-orientation. Communication pattern of conversation-orientation that applied by fathers was positively related to the dimensions of trust in attachment of father-adolescent. Communication pattern of conformity-orientation that applied by fathers was negatively related to fathers’ satisfaction levels.